The Self, consciousness and communication - Rose Marie Rose Marie Bezuidenhout (Communicare)
This article explores intrapersonal and transpersonal communication as the principal derivatives of a subjective, inner reality. These levels relate to different states and levels of consciousness and corresponding levels of selfawareness. Since an exploration of the nature of the self and its possible confluence with states and levels of consciousness necessitates a multidisciplinary approach, theories and constructs in Psychology, the New Physics (Quantum Physics), Mysticism, and Philosophy are integrated with contemporary communication notions of the self and consciousness. Integration and inclusiveness consequently form the bedrock of this article.